Microwave Synthesize Karaya Gum-Cu, Ni Nanoparticles Based Bionanocomposite as an Adsorbent for Malachite Green Dye: Kinetics and Thermodynamics - Saruchi,; Kumar, Vaneet; Ghfar, Ayman A.; Pandey, Sadanand (Frontiers in Materials, 2022)
A novel approach was used to synthesize karaya gum-Cu,Ni nanoparticles based bionanocomposite by microwave irradiation method. Synthesized bionanocomposite was characterized by different techniques like Fourier transform infrared (FTIR) spectroscopy, Field Emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), High Resolution Transmission Electron Microscopy (HR-TEM) and Electron Dispersive studies (EDS). The optimized condition for Karaya gum-Cu,Ni bionanocomposite synthesis was the amount of solvent 4 mL, pH 10, time 20 sec., power 100, monomer and cross-linker concentration 14.11 molL-1 and 0.1135 molL-1, respectively. Maximum % swelling was found to be 1176%. Different reaction parameters were optimized to get the maximum adsorption of malachite green dye. The maximum dye adsorption was found to be 94.1%. Different models for kinetics as well as isotherms were applied to analyze the adsorption data. Malachite green sorption onto bionanocomposite is best defined by pseudo second order kinetics, signifying that the dye uptake by the nanocomposite was organized by chemisorption method involving sharing of electrons in-between cationic part of dye as well as anionic part of bionanocomposite. R2 was determined to be 0.99569. The correlation coefficient values of nanocomposite best fit in the Freundlich adsorption isotherm. The synthesized bionanocomposite was an efficient adsorbent for the adsorption of the harmful dye malachite green.